2014
DOI: 10.12968/hmed.2014.75.7.391
|View full text |Cite
|
Sign up to set email alerts
|

Management of nausea and vomiting in palliative care

Abstract: Nausea and vomiting are common symptoms in palliative care and can be highly distressing to patients. This review discusses the mechanisms by which nausea and vomiting are triggered, using case studies to highlight the most common scenarios and how to manage these.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Opioids have three potentially nausea-inducing mechanisms; it has a direct effect on the chemoreceptor trigger zone, enhanced vestibular sensitivity, and delayed gastric emptying [ 10 ]. For patients with opioid-induced nausea, metoclopramide is the first-line treatment [ 11 ]. For nausea-refractory cases, atypical antipsychotics, such as olanzapine or risperidone, can be initiated [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Opioids have three potentially nausea-inducing mechanisms; it has a direct effect on the chemoreceptor trigger zone, enhanced vestibular sensitivity, and delayed gastric emptying [ 10 ]. For patients with opioid-induced nausea, metoclopramide is the first-line treatment [ 11 ]. For nausea-refractory cases, atypical antipsychotics, such as olanzapine or risperidone, can be initiated [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…If suspected, imaging should be considered, as it will provide directed symptom management. Studies have shown that metoclopramide is a reasonable initial choice for nausea management of palliative patients with unclear etiology [ 11 ]. Haloperidol is often used as a second-line drug for those who have contraindications or refractory to metoclopramide [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations